(untitled) (JURNAL ADMINISTRASI PUBLIK, 2018)
ABSTRACT : The employment issue in the Sula Islands District has now reached an appreciable condition marked by large unemployment and underemployment, relatively low and uneven incomes, on the contrary unemployment and high unemployment are a waste of human resources and potential, the burden of family and society, the main source of poverty, can encourage increased social and criminal unrest, and can hamper development in the long run, the future development of the Indonesian nation. Low unemployment rates can reflect good economic growth, and can reflect improvements in the quality of the livelihoods of the population and increased equity of income, hence the welfare of the population may then increase. Based on the description on the background above, the authors are interested in conducting research with the title "Implementation of Local Government Policy In Countering Unemployment In Sula Islands District, North Maluku Provinceâ€. Keyword : Implementation of policies, local government, unemployme